Economy-wide CO2 Emission Reduction Due to Carbon Tax in the Power Sector: A Structural Decomposition Analysis - Charles O. P. Marpaung; Ram M. Shresta (Department of Electrical Engineering, Institut Teknologi Nasional Malang, Indonesia, 2017)
In this paper, a structural decomposition analysis based on an input-output framework has been developed to examine the factors, which affect the economy-wide CO2 emission changes due to the introduction of carbon tax in the Indonesian power sector during 2011-2030. There are three major components that affect the total economy-wide change in CO2 emissions, i.e., fuel mix-, structural-, and final demand- effects. The results show that, the CO2 mitigation under the carbon tax of US200/tC would be 20.5 times higher than that with the carbon tax rate of US5/tC. The fuel mix effect is found to be most influential in reducing the CO2 emission during the planning horizon under all of the carbon tax rates considered and is followed by the final demand- and structural-effects.